Transanal Surgery: A History of taTME Ancestry - Izquierdo, Kevin M.; Salem, Jean F.; Cha, Esther; Unal, Ece; Marks, John H. (Clinics in Colon and Rectal Surgery, 2020)
Transanal total mesorectal excision (taTME) is the culmination of major developments in rectal cancer management and minimally invasive surgery. This surgical breakthrough holds great promise and excitement for the care of the rectal cancer patient. We would be remiss in discussing taTME to not acknowledge the role of transanal abdominal transanal proctosigmoidectomy, transanal endoluminal microsurgery, laparoscopy, and natural orifice transluminal endoscopic surgery that got us to this modern day explosion of the taTME approach. In this article, we detail and explain the convergence of these disparate experiences, how they culminated in the development of the taTME, and explore future directions in this field.
Keywords: rectal cancer; transanal abdominal transanal proctosigmoidectomy; transanal total mesorectal excision; natural orifice transluminal endoscopic surgery; minimally invasive surgery; transanal minimally invasive surgery; transanal endoluminal microsurgery; intersphincteric resection; total mesorectal excision